Les sépultures du Haut Moyen âge du Champs-des-Bosses à Saint-Xandre: organisation et recrutement particulier de tombes dispersées - Yves Gleize; Lionel Maurel (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
During rescue archaeology some thirty graves were discovered during the excavation of an early medieval settlement near Saint-Xandre (Charente-Maritime, France). Despite the poor preservation of the bones, the archaeo-anthropological analysis provides information about burial type and biological identity. The principal characteristic of these graves is the selection of those buried, more than 70% of which are children. The analysis of age at death and of the spatial distribution of the graves provides elements concerning the organisation of this group of burials. The locations of the graves indicate that distinctions were made within this area and enable discussion of the existence of possible changes in the spatial organisation. This discovery provides a particular example of scattered burials near a medieval rural settlement as well as new elements concerning this phenomenon.